#### Answer

-5$x^{2}$ + 3x

#### Work Step by Step

2(-5$x^{2}$ + 3x) - (3x - 5$x^{2}$)
Use the distributive property to remove the parentheses
=2.-5$x^{2}$ + 2.3x - (3x - 5$x^{2}$)
Drop parentheses and change the sign of each term in parentheses: - (3x - 5$x^{2}$) = - 3x + 5$x^{2}$
= 2.-5$x^{2}$ + 2.3x - 3x + 5$x^{2}$
Multiply
= -10$x^{2}$ + 6x - 3x + 5$x^{2}$
Group like terms
= (-10$x^{2}$ + 5$x^{2}$) + ( 6x - 3x )
combine like terms (-10$x^{2}$ + 5$x^{2}$) = (-10+5)$x^{2}$ = -5$x^{2}$, (6x - 3x) =(6-3)x = 3x
=-5$x^{2}$ + 3x